Ramsey (K_1,2,K_3)-Minimal Graphs - Borowiecki, M.; Schiermeyer, I.; Sidorowicz, E. (The Electronic Journal of Combinatorics, 2005)
For graphs G,F and H we write G→ (F,H) to mean that if the edges of G are coloured with two colours, say red and blue, then the red subgraph contains a copy of F or the blue subgraph contains a copy of H. The graph G is (F,H)-minimal (Ramsey-minimal) if G→ (F,H) but G’ ot→ (F,H) for any proper subgraph G’G. The class of all (F,H)-minimal graphs shall be denoted by R (F,H). In this paper we will determine the graphs in R(K_1,2,K_3).